Bilingual Information Hiding System: A Formalized Approach - Jabri, Riad; Ibrahim, Boran (Transactions on Engineering and Computing Sciences, 2015)
Steganogrphy and cryptography are used to maintain privacy and security over communication channels. Due to their complexity and diversity, there is a need for their continuous improvements. In this paper, we consider such improvements and propose a new bilingual information hiding system. The proposed system is based on a formal approach that incorporates text-based steganography and cryptography in a way that permits multilayered levels of security and privacy and improves the quality of information hiding in terms of perceptual transparency, robustness and hiding capacity. Considering an Arabic text as a cover one, the inter-word spaces and word features have been used as places for information hiding. As a result, 3.676 have been achieved as an improved average of capacity ratio.